LOW DOSE OF ESMOLOL ATTENUATES SEPSIS-INDUCED IMMUNOSUPPRESSION VIA MODULATING T-LYMPHOCYTE APOPTOSIS AND DIFFERENTIATION. Issue 5 (28th May 2023) - Ma, Ying; Cheng, Zhenshun; Zheng, Yong; Wang, Wei; He, Shaojun; Zhou, Xiaolian; Yang, Jiong; Wei, Chaojie
ABSTRACT: Background: Immunosuppression caused by immune cell apoptosis and an imbalance of T helper 2 cells (TH 2) and T helper 1 cells (TH 1), is associated with poor outcomes in septic patients. Esmolol was reported to improve survival by modulating immune responses in septic shock. Whether esmolol could alleviate sepsis-induced immunosuppression and the optimal dose are unclear. Methods: Four hours after cecal ligation and puncture (CLP), Wistar rats were randomized into CLP, CLP + E-5 (esmolol: 5 mg·kg −1 ·h −1 ) and CLP + E-18 (esmolol: 18 mg·kg −1 ·h −1 ) groups. Eight rats were underwent sham operation. Eighteen hours after CLP, hemodynamics and organ histological injuries were evaluated, peripheral blood mononuclear cells apoptosis and T-lymphocyte subsets counts were determined by flow cytometry, and the expression of p-Akt, Bcl-2, cleaved Caspase-3, and p-Erk1/2 in splenic CD4 + T-lymphocytes was determined by western blot and immunohistochemistry. β1 -Adrenoreceptor expressions were evaluated using real-time polymerase chain reaction and immunohistochemistry. Results: Cecal ligation and puncture induced tachycardia, hypotension, hyperlactatemia, and multiple organ injury. Heart rate was unchanged in the CLP + E-5 group but decreased in the CLP + E-18 group. Hypotension, lactatemia, and multiple organ injuries were improved only in the CLP + E-5 group. T-lymphocyte apoptosis and TH 2/TH 1 ratio was decreased in CLP + E-5 but not in CLP + E-18. p-Akt and Bcl-2 expressions were increased, while cleaved Caspase-3 and p-Erk1/2 expressions were decreased in CLP + E-5. β1 -Adrenoreceptor expressions were unchanged in both CLP + E-5 and CLP + E-18 groups. Conclusions: Low dose of esmolol reduced T-lymphocyte apoptosis and restored TH 2/TH 1 ratio in septic shock. Esmolol might modulate Akt/Bcl-2/Caspase-3 pathway to relieve T-lymphocyte apoptosis and inhibit Erk1/2 activity to decrease TH 0 differentiation to TH 2. Esmolol may be a potential immunoregulator of septic shock.